2020
DOI: 10.1021/acs.accounts.9b00531
|View full text |Cite
|
Sign up to set email alerts
|

Ensembles of Metastable States Govern Heterogeneous Catalysis on Dynamic Interfaces

Abstract: Heterogeneous catalysis is at the heart of chemical industry. Being able to tune and design efficient catalysts for processes of interest is of an utmost importance, and for this, the molecular-level understanding of heterogeneous catalysts is the first step, and indeed a prime focus of the modern catalysis research. For a long time, a single most thermodynamically stable structure of the catalytic interface attained in reaction conditions had been envisioned as the reactive phase. However, some catalytic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
214
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 201 publications
(219 citation statements)
references
References 90 publications
5
214
0
Order By: Relevance
“…The fluxionality of small clusters and its effect on catalytic activity has been discussed recently. [56][57][58][59][60][61] The non-uniformity of CO adsorption is clearly seen in the phase diagrams ( Fig. 3): some CO coverages are never the most stable.…”
Section: Co Binding and Vibrational Frequenciesmentioning
confidence: 97%
“…The fluxionality of small clusters and its effect on catalytic activity has been discussed recently. [56][57][58][59][60][61] The non-uniformity of CO adsorption is clearly seen in the phase diagrams ( Fig. 3): some CO coverages are never the most stable.…”
Section: Co Binding and Vibrational Frequenciesmentioning
confidence: 97%
“…[13] We emphasize that this amorphous interface is highly dynamic and, as such, it is as uspect for presenting metastable active sites.M etastable species may remain am inority,a nd thus be poorly detectable even by operando characterization. [23,24] Such active sites may be studied by leveraging computational tools.P revious theoretical work reveals ad ynamic BO x surface that does indeed contain metastable surface states with distinct geometries,s toichiometries,a nd chemistries,w hich can form on at imescale of picoseconds and become only significantly populated as the temperature is increased from 298 Kto763 K, based on grand canonical simulations. [9] After ruling out the BO 3 -type surface units,w eo btained three other types of sites that have > 5% population at the reaction temperature;a ll of them contain unsaturated B-B-B units in which the middle Bi sb uried in the sublayer while two ends are exposed (denoted as {BB}).…”
Section: Computational Insightsmentioning
confidence: 99%
“…[2][3][4] Recently, it has been shown that, for dynamic catalytic interfaces, metastable structures of the catalyst rather than the global minimum can play an important role in defining the thermodynamic and the kinetic properties of the interfaces. [5][6][7] Perhaps This affects their interaction with the reagents, and the resultant reaction pathways and barriers.…”
Section: Introductionmentioning
confidence: 99%